Research in the history of economic thought and methodology : including a symposium on economists and authoritarian regimes in the 20th century - Fiorito, Luca, 1967-; Scheall, Scott; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology ;, 2020)
Volume 38B of Research in the History of Economic Thought and Methodology features a symposium on economists and authoritarian regimes in the 20th century. Guest-edited by Federico D'Onofrio and Gerardo Serra, the symposium includes contributions from José Luís Cardoso, Till Düppe and Sarah Joly-Simard, Elisa Grandi, Alexandre Andrada and Mauro Boianovsky, Tinashe Nyamunda, Doriana Matraku Dervishi and Marianne Johnson, and Nicolas Brisset and Raphaël Fèvre. Volume 38B also features a new general-research essay by Reinhard Schumacher and RHETM co-editor Scott Scheall that provides new details concerning Carl Menger's life and career.